Effects of Hurricane Bret on Northern Bobwhite Survival in South Texas - Fidel Hernandez; Juan D. Vasquez; Fred C. Bryant; Andrew A. Radomski; Ronnie Howard (National Quail Symposium Proceedings, 2017)
The impacts of intense storms such as hurricanes on wildlife rarely are documented. We had the opportunity to monitor the impact of Hurricane Bret on northern bobwhite (Colinus virginianus) survival and reproduction in Brooks County, Texas. On 22 August 1999, Hurricane Bret struck our study area, which received > 45 cm of rain and experienced wind gusts >160 km/h. We documented the survival of bobwhite adults (n = 82), broods (n = 15), and nests (n = 4) via radiotelemetry before and after the hurricane. Only 11 (13%) adult bobwhites were killed, with 4 killed directly from exposure to the hurricane. Broods experienced higher mortality, with 7 (47%) broods killed during the hurricane. Six of the 7 dead broods were < 1 week old. Sizes of the 8 surviving broods were reduced from a mean brood size of about 11 chicks prior to the hurricane to a mean size of 4 after the hurricane (P = 0.01). Of the 4 nests monitored, 3 were depredated and eggs in 1 nest hatched the weekend of the storm. Hurricanes may negatively impact the survival of young (i.e., < 2 weeks old) bobwhite broods.
Keywords: Colinus virginianus; hurricane; Hurricane Bret; mortality; northern bobwhite; survival; weather